ANALISIS PENGARUH PENERAPAN METODE ARUS BIAYA PERSEDIAAN, NILAI PERSEDIAAN DAN GROSS PROFIT MARGIN TERHADAP MARKET VALUE PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Bambang Sudaryono; Hilda Hilda (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2007)
The aim of this research is to find the influence of inventory cost flow methods, inventory value and gross profit margin to the company market value. The research data was gathered from the annually financial report 56 manufacturers companies that were sampled listed on Jakarta Stock Exchange (JSX) within the period of 2002-2005. Out of the 56 manufacturer companies, forty-eight of them are implementing the average inventory cost flow method and 8 companies implemented the FIFO inventory cost flow method. These samples were chooses by applying the purposed sampling method. The analysis was calculated by using classic assumption test consists of normalization data, multicoleneritas, autocorrelation and heterousskedastisitis test. Afterwards, hypothesis test was measured by utilizing the multiple regression test followed with F test and t test also independents t test act as a support for hypothesis test. The result of this research shows that as collectively the inventory cost flow methods, inventory value and gross profit margins significantly affected the market value. And as individually, the variable that significantly affects the market values is just inventory while the inventory cost flow methods and gross profit margin had a less impact to the market value.